Brush-like Ni/carbon nanofibers/carbon nanotubes multi-layer network for freestanding anode in lithium ion batteries. Issue 13 (September 2019) - Chen, Nana; Chen, Lei; Li, Wenxiao; Xu, Zhiwei; Qian, Xiaoming; Liu, Yong
Abstrct: A brush-like Ni/carbon nanofibers/carbon nanotubes (Ni-CNFs-CNTs) multi-layer conductive network was designed to work as a freestanding anode in lithium ion batteries (LIBs). The carbon nanotubes (CNTs) arrays were grown vertically on the surface of carbon nanofibers (CNFs) with the active Ni bound on the other end of the CNTs. The intimate connection between CNFs and CNTs offers multiple transport routes for electron and ion, and the brush-like structure with gaps and super specific surface area is conducive to shorten Li + ion diffusion pathways and buffer volume expansion during the Li + insertion/extraction process. An outstanding cycling stability (480.82 mAh g −1 after 100 cycles at 100 mA g −1 and 260.88 mAh g −1 after 1000 cycles at 1000 mA g −1 ) and an excellent rate capacity (262.06 mAh g −1  at 1000 mA g −1 ) were achieved as a freestanding anode in LIBs.